Utilização do método de franjas de Moiré na análise da influência da lesão cervical não cariosa, material restaurador e carregamento oclusal no padrão de deformação de pré-molares superiores - Milito, Giovana de Almeida (2013)
The aim of this study was to use the projection Moiré technique for the analysis of deformation occurring in the dental structure. The influence of non-carious cervical lesions (NCCL), mesio-occlusal-distal (MOD) cavity restored with different materials and occlusal loading type on the deformation of premolars. Eighteen premolars were randomly distributed into 6 groups (n = 3). Group A: MOD cavity restored with amalgam, AL: amalgam MOD + not restored NCCL; ALR: amalgam MOD + restored NCCL; R: composite resin MOD; RL: composite resin MOD + not restored NCCL; RLR: composite resin MOD + restored NCCL. The samples were subjected to two types of occlusal loading: axial and thereafter, 30° oblique. The deformations occurring were analyzed by the projection Moiré method in mesiobuccal dital (MD), cervical occlusion (CO) and bucco-lingual (BL) directions. The results showed that groups with not restored NCCL showed higher strain values in both CO and MD analysis directions, regardless of the type of occlusal loading. The AL group when subjected to oblique loading showed the highest strain values in both CO and MD directions. Toward BL direction the loading type and MOD cavity restorative material type influence the deformation of the samples. From the results of this study it was concluded that by the projection Moiré technique it is possible to quantify the deformations that occur in the tooth structure and that the presence of NCCL, the type of occlusal loading and MOD cavity restorative material type influence the deformation upper pre- molars.